Smart Healthcare - Heston, Thomas F. (IntechOpen, 2020)
Over the last 150 years, advances in technology have revolutionized health care and as a result increased the average human lifespan by approximately 50%. Smart medicine is the use of algorithms and automated technology in health care, and it is anticipated that advances in this area of artificial intelligence will help lead to even further gains in health and longevity. This collection of the latest thinking by experts in the field of smart medicine will help readers learn about some of the latest developments in smart technology as applied to the field of medicine.